Are leaf traits and genetic differentiation patterns divergent in endemic vs widespread congeneric plant species? Insights from the Mediterranean forest species pair Aegonychon calabrum-A. purpurocaeruleum (Boraginaceae) - Andrea Coppi; Giacomo Santini; Roberto Canullo; Elisa Carrari; Stefano Chelli; Emmanuele Farris; Cristina Gasperini; Leonardo Rosati; Ilaria Santi; Enrico Bajona; Giandiego Campetella; Federico Selvi (Plant Biosystems, 2026)
Understanding trait and genetic variability within endemic plant species is key to elucidate their plasticity, resource-use attitudes and adaptive responses in variable habitat conditions. However, no studies have focused on both variability dimensions and their relationship in narrow Mediterranean endemics of the forest understorey. We investigated this topic in the species pair Aegonychon calabrum , a rare herb in southern Italy, and its related widespread congener A. purpurocaeruleum (Boraginaceae). After assessing intraspecific variation in Leaf Area (LA), Specific Leaf Area (SLA), Leaf Dry Matter Content (LDMC), and population genetic structure by AFLP fingerprinting, we used P ST –F ST comparisons to infer the proportion of genotypic and phenotypic differentiation driven by directional vs. stabilizing selection. We also examined whether individuals exhibit similar trait values due to their genetic proximity. Lower LA suggested lower resource-acquisitive ability in A. calabrum , but variation in traits and CSR scores was comparable to its widespread congener. Population heterozygosity was slightly lower than in A. purpurocaeruleum, not supporting genetic erosion in the endemic species. In both species, phenotypic differentiation was higher than genetic differentiation suggesting that directional or divergent selection is potentially acting on the examined leaf traits and thus on their resource use attitudes. Trait values positively correlate with genetic proximity in a clade formed by two of the three A. calabrum populations, a pattern consistent with population-level niche conservatism. The case study of A. calabrum supports that, while generally fitting the "refuge" model, populations of endemic understory herbs of Mediterranean forests can be subject to non-stabilizing selection.

From ashes to old-growth forests: How do long-term changes in forest structure affect understory plant diversity after wildfires in Yellowstone National Park? - Zhengxue Zhu; Robert W. Pal; Stefano Chelli; Marco Cervellini; Roberto Canullo; Luciano Ludovico Maria De Benedictis; Alysia Cox; Ariana Rivera Añazco; Sandor Bartha; Giandiego Campetella (Forest Ecology and Management, 2026)

Three ectomycorrhizal fungal inoculum modifies the growth performance and tolerance of Quercus nuttallii seedlings under salt stress - Nan Yang; Cheng Wan; Daoyuan Ren; Yan Zhang; Stefano Chelli; Zhengxue Zhu; Silvia Traversari; Giovanni Emiliani; Lingfeng Mao (Forest Ecology and Management, 2026)

Soil biodiversity and ecosystem functions in grasslands: Is more always better? - Dajana Radujković; Miguel Portillo-Estrada; Björn Hendrickx; Giandiego Campetella; Willem-Jan Emsens; Mária Höhn; Gerald Jurasinski; Stefano Chelli; Tim Vochten; Erik Verbruggen (Soil Biology and Biochemistry, 2025)

ITV-net: a dataset of intraspecific leaf traits data across major Italian habitats - Stefano Chelli; Alessandro Bricca; Francesco Petruzzellis; Enrico Tordoni; Giacomo Calvia; Alicia T.R Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; et al. (Plant Biosystems, 2025)

How effective are different protection strategies in promoting the plant diversity of temperate forests in national parks? - Zhengxue Zhu; Stefano Chelli; James L. Tsakalos; Alessandro Bricca; Roberto Canullo; Marco Cervellini; Riccardo Pennesi; Luciano L.M. De Benedictis; Vanessa Cesaroni; Alessandro Bottacci; Giandiego Campetella (Forest Ecology and Management, 2025)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Multiple drivers of functional diversity in temperate forest understories: Climate, soil, and forest structure effects - Stefano Chelli; Alessandro Bricca; James L. Tsakalos; Anna Andreetta; Gianmaria Bonari; Giandiego Campetella; Stefano Carnicelli; Marco Cervellini; Nicola Puletti; Camilla Wellstein; Roberto Canullo (Science of The Total Environment, 2024)

Intraspecific variability of leaf form and function across habitat types - Giacomo Puglielli; Alessandro Bricca; Stefano Chelli; Francesco Petruzzellis; Alicia T. R. Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; Giacomo Calvia; et al. (Ecology Letters, 2024)
Trait‐based ecology has already revealed main independent axes of trait variation defining trait spaces that summarize plant adaptive strategies, but often ignoring intraspecific trait variability (ITV). By using empirical ITV‐level data for two independent dimensions of leaf form and function and 167 species across five habitat types (coastal dunes, forests, grasslands, heathlands, wetlands) in the Italian peninsula, we found that ITV: (i) rotated the axes of trait variation that define the trait space; (ii) increased the variance explained by these axes and (iii) affected the functional structure of the target trait space. However, the magnitude of these effects was rather small and depended on the trait and habitat type. Our results reinforce the idea that ITV is context‐dependent, calling for careful extrapolations of ITV patterns across traits and spatial scales. Importantly, our study provides a framework that can be used to start integrating ITV into trait space analyses.

Consistent predictors of microbial community composition across spatial scales in grasslands reveal low context‐dependency - Dajana Radujković; Sara Vicca; Margaretha van Rooyen; Peter Wilfahrt; Leslie Brown; Anke Jentsch; Kurt O. Reinhart; Charlotte Brown; Johan De Gruyter; Gerald Jurasinski; Diana Askarizadeh; Sandor Bartha; et al. (Molecular Ecology, 2023)
Environmental circumstances shaping soil microbial communities have been studied extensively. However, due to disparate study designs, it has been difficult to resolve whether a globally consistent set of predictors exists, or context‐dependency prevails. Here, we used a network of 18 grassland sites (11 of those containing regional plant productivity gradients) to examine (i) if similar abiotic or biotic factors predict both large‐scale (across sites) and regional‐scale (within sites) patterns in bacterial and fungal community composition, and (ii) if microbial community composition differs consistently at two levels of regional plant productivity (low vs. high). Our results revealed that bacteria were associated with particular soil properties (such as base saturation) and both bacteria and fungi were associated with plant community composition across sites and within the majority of sites. Moreover, a discernible microbial community signal emerged, clearly distinguishing high and low‐productivity soils across different grasslands independent of their location in the world. Hence, regional productivity differences may be typified by characteristic soil microbial communities across the grassland biome. These results could encourage future research aiming to predict the general effects of global changes on soil microbial community composition in grasslands and to discriminate fertile from infertile systems using generally applicable microbial indicators.

Beyond commonplace: effects of coppice management on understory plants. Evidences from Italian forests - Stefano Chelli; Marco Cervellini; Giandiego Campetella; Roberto Canullo (Plant Biosystems, 2023)

Environmental and pedological factors influencing organic carbon storage in Italian forest soils - Anna Andreetta; Stefano Chelli; Eleonora Bonifacio; Roberto Canullo; Guia Cecchini; Stefano Carnicelli (Geoderma Regional, 2023)

Diachronic Observations Reveal Different and Scale-Dependent Response of Sand Dune Plants to Seashore Dynamics - Stefano Chelli; Fabio Conti; Luca Bracchetti (Estuaries and Coasts, 2022)

Species trait syndrome drives the leaves’ functional variations of dominant grasses to modifications in summer water supply - Federico Maria Tardella; Alessandro Bricca; Stefano Chelli; Giandiego Campetella; Roberto Canullo; Maurizio Cutini; Irina G. Goia; Nicola Postiglione; Andrea Catorci (Plant Ecology, 2021)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Contrasting patterns in leaf traits of Mediterranean shrub communities along an elevation gradient: measurements matter - Giandiego Campetella; Stefano Chelli; Camilla Wellstein; Emmanuele Farris; Giacomo Calvia; Enrico Simonetti; Lubov Borsukiewicz; Sula Vanderplank; Michela Marignani (Plant Ecology, 2019)

Groundwater characterization from an ecological and human perspective: an interdisciplinary approach in the Functional Urban Area of Parma, Italy - Andrea Zanini; Emma Petrella; Anna Maria Sanangelantoni; Letizia Angelo; Beatrice Ventosi; Luca Viani; Pietro Rizzo; Sara Remelli; Marco Bartoli; Rossano Bolpagni; Alessandro Chelli; Alessandra Feo; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Litter decomposition: effects of temperature driven by soil moisture and vegetation type - Alessandro Petraglia; Cecilia Cacciatori; Stefano Chelli; Giuseppe Fenu; Giulia Calderisi; Domenico Gargano; Thomas Abeli; Simone Orsenigo; Michele Carbognani (Plant and Soil, 2019)

Effects of extreme drought on specific leaf area of grassland species: A meta‐analysis of experimental studies in temperate and sub‐Mediterranean systems - Camilla Wellstein; Peter Poschlod; Andreas Gohlke; Stefano Chelli; Giandiego Campetella; Sergey Rosbakh; Roberto Canullo; Jürgen Kreyling; Anke Jentsch; Carl Beierkuhnlein (Global Change Biology, 2017)
Here, we conducted a meta‐analysis of experimental drought manipulation studies using rainout shelters in five sites of natural grassland ecosystems of Europe. The single studies assess the effects of extreme drought on the intraspecific variation of the specific leaf area ( SLA ), a proxy of plant growth. We evaluate and compare the effect size of the SLA response for the functional groups of forbs and grasses in temperate and sub‐Mediterranean systems. We hypothesized that the functional groups of grasses and forbs from temperate grassland systems have different strategies in short‐term drought response, measured as adjustment of SLA , with SLA ‐reduction in grasses and SLA ‐maintenance in forbs. Second, we hypothesized that grasses and forbs from sub‐Mediterranean systems do not differ in their drought response as both groups maintain their SLA . We found a significant decrease of SLA in grasses of the temperate systems in response to drought while SLA of forbs showed no significant response. Lower SLA is associated with enhanced water‐use efficiency under water stress and thus can be seen as a strategy of phenotypic adjustment. By contrast, in the sub‐Mediterranean systems, grasses significantly increased their SLA in the drought treatment. This result points towards a better growth performance of these grasses, which is most likely related to their strategy to allocate resources to belowground parts. The observed SLA reduction of forbs is most likely a direct drought response given that competitive effect of grasses is unlikely due to the scanty vegetation cover. We point out that phenotypic adjustment is an important driver of short‐term functional plant response to climatic extremes such as drought. Differential reactions of functional groups have to be interpreted against the background of the group's evolutionary configuration that can differ between climatic zones.

Adaptation of the Canadian Fire Weather Index to Mediterranean forests - Stefano Chelli; Pierluigi Maponi; Giandiego Campetella; Paolo Monteverde; Monica Foglia; Eleonora Paris; Andreas Lolis; Thomas Panagopoulos (Natural Hazards, 2015)

Intraspecific phenotypic variability of plant functional traits in contrasting mountain grasslands habitats - Camilla Wellstein; Stefano Chelli; Giandiego Campetella; Sandor Bartha; Marco Galiè; Francesco Spada; Roberto Canullo (Biodiversity and Conservation, 2013)

Peripheral-type benzodiazepine receptor binding sites in platelets of patients with panic disorder associated to separation anxiety symptoms - Stefano Pini; Claudia Martini; Marianna Abelli; Matteo Muti; Camilla Gesi; Marina Montali; Beatrice Chelli; Antonio Lucacchini; Giovanni B. Cassano (Psychopharmacology, 2005)